Structure-based design of an RNA-binding zinc finger - McColl, Damian J. (The National Academy of Sciences, 1999)
A structure-based approach was used to design RNA-binding zinc fingers that recognize the HIV-1 Rev response element (RRE). An arginine-rich α-helix from HIV-1 Rev was engineered into the zinc finger framework, and the designed fingers were shown to bind specifically to the RRE with high affinity and in a zinc-dependent manner, and display cobalt absorption and CD spectra characteristic of properly folded fingers. The results indicate that a monomeric zinc finger can recognize a specific nucleic acid site and that the α-helix of a finger can be used to recognize the major groove of RNA as well as DNA. The RRE-binding zinc fingers demonstrate how structure-based approaches may be used in the design of potential RNA-binding therapeutics and provide a framework for selecting RNA-binding fingers with desired specifications.